Analysis of Respiratory Sinus Arrhythmia with Respect to Respiratory Phase - Kotani, K.; Hidaka, I.; Yamamoto, Y.; Ozono, S. (Methods of Information in Medicine, 2000)
We evaluated the respiratory modulation of heart rate, i.e., respiratory sinus arrhythmia (RSA), with respect to respiratory phase derived from an analytic signal from the lung volume curve, during spontaneous breathing and paced breathing with different patterns. The magnitudes and waveforms of RSA in the phase domain were similar regardless of breathing pattern, even including spontaneous breathing. An examination of the occurrence of heart beats with respect to the respiratory phase revealed that synchronized patterns recently reported in the literature (Nature 392: 239, 1998) were observed during paced breathing with breath holding periods whereby the respiratory phase advanced more slowly. It was concluded that the phase domain approach might be useful in extracting RSA during spontaneous breathing and for elucidating detailed mechanisms for RSA. However, the use of this technique for studies investigating cardio-respiratory coupling should be approached cautiously, as the results may be influenced by breathing patterns.
Keywords: Respiratory Sinus Arrhythmia; Respiratory Phase; Hilbert Transform